2016
DOI: 10.4183/aeb.2016.185
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Malignancy Risk of Incidental Thyroid Nodules in Patients with Non-Thyroid Cancer

Abstract: Context. Thyroid incidentaloma is a common disorder in endocrinology practice. Current literature regarding the risk of thyroid cancer in incidentalomas found in patients with non-thyroid cancer is limited.Objective. The aim of the present study was to investigate the frequency of thyroid malignancy in thyroid incidentalomas detected in patients with non-thyroid cancer.Design. Case control study. Subjects and Methods. The database of 287 thyroid nodules from 161 patients with a history of nonthyroid cancer fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In our study, thyroid gland was the most frequent site because suspicious lesions (72 out of 304) with high FDG uptake can be detected easily by visual assessment, due to the relatively low physiological FDG uptake of normal thyroid tissue. Although some benign thyroid pathologies such as thyroiditis, Grave's disease, or post-immunotherapy changes may cause increased FDG uptake, they are often diffuse in pattern, while focal hypermetabolic thyroid lesions may represent focal hyperplasia or malignancy [6,7]. Studies showed that 30.9% of focal hypermetabolic thyroid lesions are malignant, suggesting about 70% being false positive [8].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, thyroid gland was the most frequent site because suspicious lesions (72 out of 304) with high FDG uptake can be detected easily by visual assessment, due to the relatively low physiological FDG uptake of normal thyroid tissue. Although some benign thyroid pathologies such as thyroiditis, Grave's disease, or post-immunotherapy changes may cause increased FDG uptake, they are often diffuse in pattern, while focal hypermetabolic thyroid lesions may represent focal hyperplasia or malignancy [6,7]. Studies showed that 30.9% of focal hypermetabolic thyroid lesions are malignant, suggesting about 70% being false positive [8].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding follicular thyroid carcinomas, the molecular pathogenesis is still controversial. Oncogenic activation due to Ras point mutations is present both in follicular adenomas and carcinomas (17,19), including the oncocytic follicular carcinoma (20,21). This oncogene is involved in the cellular signal transduction and mutations induce a continuous proliferation of cells, inevitably leading to cancer.…”
Section: Discussionmentioning
confidence: 99%